The role of trade unions in sport - the essence, features and perspectives - Matuszak, Michał (Journal of Education, Health and Sport, 2022)
Trade unions play an important role in organizing activities in the field of labour law, although some representatives of the doctrine believe that the ruling powers of trade unions are in fact administrative in nature. The role of trade unions is important in all sectors of the economy, including sports. In many European countries, trade unions in sport play a key role in ensuring that players’ right are respected. The potential of trade unions in Poland is still not fully used. The aim of this article is to analyse the role of trade unions in sport by determining their features and perspectives, in particular taking into account the extension of the subjective scope of the coalition right after the amendment to the Trade Unions Act. The deliberations will lead to an answer to the question: Is it finally time for trade unions in the professional sport sector or is it still a distant perspective? The article uses the dogmatic and legal method, and also indicates foreign solutions in relation to the comparative method. The considerations present legal solutions in the USA, England and the Netherlands. The deliberations concern both labor law and sports law. The main conclusion from the conducted research is that there are formal and legal possibilities for trade unions to play a more important role in the medium and long term, however, there is no specific entity or group of entities that would be really interested in their development, both among the athletes themselves as well as in sports clubs and Polish sports associations or the Ministry of Sport.